A LEGAL PROTECTION FOR CONSUMERS FOR NON-CONFORMITY OF GOODS PURCHASED ONLINE THROUGH THE SHOPEE APPLICATION IS LINKED TO LAW NUMBER 8 OF 1999 CONCERNING CONSUMER PROTECTION - Saepuloh, Saepuloh; Maulana, Ihsan (Pergunu Jawa Barat, 2024)
With the existence of e-commerce buying and selling, it allows people to make more efficient buying and selling where the parties do not need to meet in person, therefore consumers cannot see and touch directly the goods they want to buy but only see through photos displayed by the seller on the internet. However, as regulated in Article 4 of the Consumer Protection Law No. 8 of 1999, namely Consumers or buyers have rights including comfort, security, and safety in consuming products or services and choosing them according to the exchange rate and conditions according to the agreement, but in reality many consumers experience losses due to e-commerce buying and selling transactions such as the goods that arrive in the hands of consumers do not match the photos of the goods on the internet. This study aims to determine (1) legal protection against non-conformity of goods purchased through the Shopee application according to Law Number 8 of 1999 concerning Consumer Protection, (2) dispute resolution when the goods we buy do not match what is stated in the Shopee application. The type of research used in this study is the empirical legal method with a quantitative approach and data collection techniques through interviews as primary data and collection of library data contained in books, articles or journals and legislation related to the problem being studied. The conclusion that can be drawn is that the public does not understand well about consumer rights that must be protected in order to avoid losses from business actors and the Consumer Protection Law only regulates traditional buying and selling such as in the market while the ITE Law regulates electronic transactions only, not specifically written for buying and selling in detail.